THE ROLE OF MERGERS AND ACQUISITIONS IN ENHANCING BANK EFFICIENCY IN NIGERIA - Okoro, Chinedu Benjamin; Adebowale, Grace Ngozi (Ayden Journal of Management and Social Sciences, 2024)
The banking sector stands as a cornerstone of any nation's economy, wielding significant influence over its financial stability and growth trajectory. Recognizing the pivotal role of banks, governments often undertake reform processes to enhance their efficiency and forestall potential distress. In Nigeria, the banking sector has been subject to a comprehensive reform agenda, aligning with the government's strategic objectives of integrating into the African regional and global financial systems. This abstract explores the evolution of the Nigerian banking sector and the transformative impact of reform initiatives. As highlighted by Akpan (2007), the sector has undergone notable changes, including shifts in the number of institutions, ownership structures, and the scope of operations. These changes reflect the dynamic nature of the Nigerian banking landscape and the proactive measures undertaken to ensure its soundness and resilience. The reform process in the Nigerian banking sector is driven by a commitment to enhancing financial performance, fostering stability, and promoting integration into broader financial ecosystems. By repositioning banks to align with international standards and best practices, Nigeria aims to strengthen its financial system's competitiveness and contribute to sustainable economic development. This abstract offers insights into the reform trajectory of the Nigerian banking sector, underscoring its significance in the broader context of economic governance and financial stability. Understanding the dynamics of banking reform in Nigeria is crucial for policymakers, regulators, and stakeholders seeking to navigate the complexities of financial governance and promote inclusive economic growth